Evaluasi Penyelenggaraan Program Sekolah Ramah Anak di SDN Jetis 3 Lamongan Menggunakan Model CIPP (Context, Input, Process, Product) - Avinda, Avicarizta Zunia; Zativalen, Oriza; Huda, Mochammad Miftachul (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The Child-Friendly School (CFS) Program is an effort to create a safe, comfortable, inclusive learning environment that protects children's rights. Although it has been implemented in various schools, its implementation still requires evaluation to ensure its compliance with the CFS indicators and to identify aspects that need improvement. This study aims to describe and evaluate the implementation of the Child-Friendly School Program at SDN Jetis 3 Lamongan based on the Context, Input, Process, and Product (CIPP) evaluation model. The study used a qualitative evaluative approach with the principal, teachers, students, and related parties as subjects. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model with source and technique triangulation to ensure data validity. The results show that the context aspect has been supported by school policies and the commitment of the school community; the input aspect has adequate resources and facilities, but program administration and documentation still need to be strengthened; the process aspect shows the implementation of participatory, inclusive, and discrimination-free learning; while the product aspect shows an increase in learning comfort, discipline, and student character. It was concluded that the implementation of the Child-Friendly School Program at SDN Jetis 3 Lamongan had gone well, but required strengthening of administration, documentation, and sustainable program development.